Can dance and health-related training be effective in helping women quit smoking? - Szmyt, Grażyna; Podgórski, Tomasz; Szmyt, Agnieszka; Gronek, Joanna; Celka, Roman; Jakubowski, Konrad (Akademia Wychowania Fizycznego w Poznaniu)
Smoking as a major social and health problem in 20-30-year-old women. About 70% nicotine addicted are determined to kick the habit with the aid of one of available smoking quitting methods such as medication, behavioral therapy, self-control or group support. Authors analyze different smoking quitting programs
Keywords: nicotine addiction; therapeutic programmes